Determinants of Quality of Regional Financial Reports in Central Java Province Using Fraud Triangle Theory - Dewi Sinto; Evi Maria (Program Studi Akuntansi FPEB UPI, 2023)
Main Purpose - The research aims to find empirical evidence of the determinants of the quality of regional financial statements in Central Java Province from the perspective of the fraud triangle theory.Method - The research sample is limited to local government financial reports in Central Java Province for the 2016-2019 fiscal year, with a total sample of 175 observations. Data were analyzed using multiple linear regression analysis.Main Findings - The research results found that pressure and rationalization did not affect the quality of financial reports in the regional government of Central Java Province. Meanwhile, the opportunity negatively influence the local government’s financial information quality. The higher the opportunity to cheat, the lower the quality of local government financial statements, and vice versa.Theory and Practical Implications – The theoretical implication is that this research finds empirical evidence that local government financial reports will be of higher quality if the opportunity to commit fraud is low. While the policy implications for the government, implementing good supervision is needed so that the opportunity for cheating is reduced and the financial reports presented can be of good quality.Novelty – The novelty of this research is the use of fraud theory, namely the fraud triangle theory, to explain the factors that affect the quality of financial reports in local governments. So far, research in the field of Public Accounting has focused chiefly on researching changes in accounting methods, so research linking fraud theory and the quality of financial reports in local governments is still limited in number.